2008
DOI: 10.1016/j.combustflame.2008.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of the effect of oxygenated blending compounds on soot formation in shock tubes

Abstract: This numerical study deals with the influence of blends on the amount of soot formed in shock tubes, which were simulated by assuming a homogeneous plug flow reactor model. For this purpose, first, the reaction model used here was validated against experimental results previously obtained in the literature. Then, the soot volume fractions of various mixtures of methyl tert-butyl ether (MTBE)-benzene, isobutene-benzene, methanol-benzene, and ethanol-benzene diluted in argon were simulated and compared to the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The present work is focusing on the following pollutants: CO, NOx, and unburned hydrocarbons (UHC) addressing acetylene and benzene considered as the major precursors of particles and soot [31][32][33][34][35][36][37]. Soot is formed 5 GTP-16-1529 -Braun-Unkhoff © 2016 by ASME.…”
Section: Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present work is focusing on the following pollutants: CO, NOx, and unburned hydrocarbons (UHC) addressing acetylene and benzene considered as the major precursors of particles and soot [31][32][33][34][35][36][37]. Soot is formed 5 GTP-16-1529 -Braun-Unkhoff © 2016 by ASME.…”
Section: Emissionsmentioning
confidence: 99%
“…Acetylene (C 2 H 2 ) and benzene (C 6 H 6 ) plays an important role in the formation of polyaromatic hydrocarbons (PAH) considered as major building blocks in soot formation [31][32][33][34][35][36][37]. Therefore, benzene and C 2 H 2 emission profiles serve as an indicator for a fuel's sooting tendency.…”
Section: Emissions Of Soot Particlesmentioning
confidence: 99%
“…A schematic diagram describing major pathways from fuel-break-up, aromatics to PAH and soot particles is given in Fig. 2; for details see [34][35][36][37][38]. Major emissions when burning kerosene in a jet engine [33] For a stoichiometric mixture and an ideal and complete combustion (no pollutants), CO 2 and water are the only products, besides energy released.…”
Section: Emissionsmentioning
confidence: 99%
“…Another route of suppression effect of ethanol additives is the formation http of H 2 O after decomposition of ethanol and consequent consumption of hydrogen atoms, that promote HACA mechanism of surface growth of carbon particles, with production of OH and H 2 [8]. On the other hand, a small amount -10% replacement of benzene by oxygenated additives (MTBE, methanol, ethanol, isobutene) can promote the carbon particle formation due to peculiarity of the kinetics of blend pyrolysis [10]. The experimental study [4] showed an increase of soot amount in shock tube pyrolysis of 1% toluene + (1-3)% ethanol mixtures.…”
Section: Introductionmentioning
confidence: 99%